Ina BORNKESSEL-SCHLESEWSKY; Matthias SCHLESEWSKY. Processing syntax and morphology. A neurocognitive perspective. Oxford: Oxford University Press. 2009. 360 pp. ISBN: 978-0-19-920782-4 - Rodrigues, Alexandra Soares (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
.